2009
DOI: 10.1177/0883911509349143
|View full text |Cite
|
Sign up to set email alerts
|

Heparinized Micropatterned Surfaces for the Spatial Control of Human Mesenchymal Stem Cells

Abstract: In this study, a heparinized micropattern surface was prepared for the spatial control of human mesenchymal stem cells (hMSCs) that can differentiate into the desired tissues. Poly(styrene-co-vinylbenzyl N,N-diethyldithiocarbamate) (poly(ST-co-VBDC)) was synthesized as a photoreactive polymer; poly(ethylene glycol) methacrylate (PEGMA) was polymerized on the poly(ST-co-VBDC) coated surface by UV irradiation. XPS spectra revealed the residual DC moieties on the PEGMA-grafted surface and the linear chain growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The higher hMSC adhesion and proliferation on pKL surfaces could be related to heparin adsorption since it was previously demonstrated that heparin immobilized on anti-adhesive surfaces increased hMSC adhesion [31].…”
Section: Discussionmentioning
confidence: 92%
“…The higher hMSC adhesion and proliferation on pKL surfaces could be related to heparin adsorption since it was previously demonstrated that heparin immobilized on anti-adhesive surfaces increased hMSC adhesion [31].…”
Section: Discussionmentioning
confidence: 92%